2007
DOI: 10.1016/j.nima.2007.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivation at a clinical LINAC: The reaction slightly above threshold

Abstract: The properties of a clinical LINAC are investigated for a study of photoactivation cross-sections slightly above the neutron threshold. As an example, the photoactivation of a tiny amount of gold by the 197 Auðg; nÞ 196 Au reaction has been measured. The derived photon intensity is at least comparable to conventional and widely used photon sources. In combination with its extremely stable operation, a clinical LINAC ensures that photoactivation studies can be performed for a wide number of targets with very li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…Photon scattering [6] and photoactivation of 176 Lu [7] have been measured using bremsstrahlung at the Stuttgart dynamitron, and earlier experiments with bremsstrahlung have been performed using medical and technical electron accelerators [8,9,10,11] which are known to provide high photon intensities [12]. Activation after Coulomb excitation was studied at the Tandem accelerator at IPN, Orsay [13], activation using positron annihilation was measured at the Kyoto research reactor [14], and photoactivation experiments with various radioactive sources were reported in [10,15,16,17].…”
Section: Equilibriummentioning
confidence: 99%
“…Photon scattering [6] and photoactivation of 176 Lu [7] have been measured using bremsstrahlung at the Stuttgart dynamitron, and earlier experiments with bremsstrahlung have been performed using medical and technical electron accelerators [8,9,10,11] which are known to provide high photon intensities [12]. Activation after Coulomb excitation was studied at the Tandem accelerator at IPN, Orsay [13], activation using positron annihilation was measured at the Kyoto research reactor [14], and photoactivation experiments with various radioactive sources were reported in [10,15,16,17].…”
Section: Equilibriummentioning
confidence: 99%
“…Photon induced reactions also play a key role in astrophysical processes where heavy, neutron deficient nuclei are synthesized by a series of photonuclear reactions. 9 These reactions are important for understanding of element creation processes in space. In the literature, there are many examples of photonuclear reaction such as food analysis, 10 chlorine and halogen analysis, 11 international safeguards and security, 12 characterization of geological, biological and environmental materials.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, 197 Au(,n) 196 Au phtonuclear reaction by using a cLINAC was carried out by Mohr et al (2007). They reported that the cLINAC is a perfect photon source in photonuclear experiments.…”
Section: Introductionmentioning
confidence: 99%